Опыт проведения онлайн-конференций - Войченко, А.П. (Управляющие системы и машины, 2016)
Дан анализ особенностей проведения онлайн-конференций на примере конференции «Новые информационные технологии в образовании для всех». Рассмотрены основные этапы реализации совокупности мер и решений, направленных на достижение максимального охвата участников конференции, выступающих как в роли докладчика, так и в роли слушателя. Подано аналіз особливостей проведення онлайн-конференцій на прикладі конференції «Нові інформаційні технології в освіті для всіх». Розглянуто основні етапи реалізації сукупності заходів та рішень, спрямованих на досягнення максимального охвату учасників конференції, що виступають як у ролі доповідачів, так і в ролі слухачів. The recent years are characterized by the rapid development of telecommunications. This can be also applied to the area of media, in particular the organization and carrying out videoconferences, production and watching the streaming video, increasing the availability of digital video resources for mobile devices, etc. As the result of the rapidly changed conditions there became actual a problem of practical use of the more affordable and available technologies for organizing and supporting the on-line conferences. This paper deals with the problems of the optimal technologies selection for recording, editing and disseminating to a wide audience the video presentations; selection of an optimal platform for the organization of live streaming with the need to maximize the coverage of the target audience; the development and implementation of the effective feedback mechanisms, which would allow a wider audience to participate in the on-line conference, and would ensure the necessary level of involvement in its work. The main stages of the measures sets and decisions taken to achieve maximum coverage targets to distribute the audience with the provision of opportunities to participate in the conference both as a speaker and as a listener are presented. The technical solutions and the experience of the practical implementation provided here can be used for the organization of the similar scientific and educational activities. The integrated approach is proposed, which is based on maximizing the cloud infrastructure and public on-line services use. It gives an opportunity to provide the high performance technical solutions without the significant resources, time and efforts investment.